Development of Rainfall Intensity-Duration-Return Period Equation for Solapur District, Maharashtra - Barai, V.N. (Journal of Soil and Water Conservation, 2022)
Rainfall intensity-duration-return period equations and nomographs for various stations are required for design of soil conservation and runoff disposal structure and for planning flood control projects. The rainfall charts of 17 years of Solapur (Maharashtra) were analyzed in the form of annual maximum series of various duration viz; 5,10,15,30 min., and 1,3,6,12 and 24 hours. The values of "a" and "b" were determined by using graphical method and the values of "K" and "d" by least square method. M The values of constants K, a, b and d were found to be 11.08, 0.1892, 1.01 and 1.2066 respectively. Abstract: